Leading Schools Moving from Issues and Challenges to Potential Solutions in School Education - Bakshi, Shivani; Awasthi, Kashyapi (JOURNAL OF INDIAN EDUCATION, 2019)
School education in the country is expanding; availability and accessibility are no longer the issues. However, achieving quality education entails strengthening schools, building effective support systems, and ensuring inclusive and safe environment. The paper highlights the role of school heads in transforming schools from government mandated institutes to self-evolving and learning organisations. The authors argue for critical engagement of the school head in addressing the key issues in school education. The study, through descriptive survey from twelve government schools across south and south-west zones of Delhi, examines the leadership practices and support systems created at school level for overall school improvement. While school heads, in the present context, are discursively repositioned as non-experts, the last in the line of management hierarchy, the paper argues on the significant role played by them through narratives from the sample schools. These elaborate the contemporary leadership practices adopted by them to retain students and enable them to complete their education.